ANALISIS PENGENDALIAN KUALITAS PRODUKSI PADA PT TESE MANUFACTURING INDONESIA - R Simanjuntak, Tommy Joshua; Aji Prasetyo, Bahariandi (Computer Science and Industrial Engineering, 2025)
This study aims to analyze and identify the causes of defective products in SENSOR - SSIC XCKN type lenses and propose quality control improvement efforts at PT TESE Manufacturing Indonesia. The main problem faced by the company is the high rate of rejected products exceeding the company's tolerance limit of 40%, with an average defect rate of 53.32% during the period of April 2024 to March 2025. Data show defect peaks in October 2024 (58,98%) and february 2025 (54,90%), which impact quality degradation, increased production costs, and potential losses. The method used in this research is Lean Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Through the Define phase, product defect issues are identified. The Measure phase is conducted to collect defect data and calculate the current DPMO (Defects Per Million Opportunities) and sigma level. In the Analyze phase, the root causes of defects will be identified using statistical tools such as Cause and Effect Diagrams and Pareto Charts. The Improve phase will formulate effective improvement solutions to reduce the defect rate. Finally, the Control phase will establish monitoring mechanisms to ensure the sustainability of improvements. After improvements were made, the product defect rate decreased to 38.69% of the established tolerance limit. It is expected that this research can provide concrete solutions to significantly reduce the number of defective products, improve production process efficiency, and help PT TESE Manufacturing Indonesia achieve better quality standards, moving towards a zero defect level and enhancing the company's competitivenes